Veins of poison: intersections of green criminology, environmental justice, and toxicity in Ambikasutan Mangad’s Swarga - Jana, Pooja; C.V., Padmaja (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this anthropocentric era, toxicity has become inseparable from ecocritical and environmental discourse. All of Life is contaminated by toxic agencies, affecting natural resources, humans and non-humans. Green Criminology as a study considers such contamination a criminal act, as it also incorporates disciplines like Environmental justice and rights to raise concerns for the environment and find solutions that would eradicate such acts of environmental 'violence'. This article establishes that fiction is a medium to unearth this crime committed against the earth, relaying Environmental rights and justice as it remains closely intertwined with human and non-human lives. Arguing that novels allow deeper introspection into environmental violence from a cultural and personal perspective, the article explores this intersection of green crime, environmental and human rights, toxicity and awareness through Ambikasutan Mangad's novel Swarga, deploying how narratives of victims and descriptions of the land and faith add to conversations of criminology, aiding the enforcement of environmental justice.